2017
DOI: 10.1080/15332640.2016.1255580
|View full text |Cite
|
Sign up to set email alerts
|

Harmful alcohol use and alcohol-related sex expectancies as predictors of risky sex among african american female college drinkers

Abstract: African American college women are experiencing sex-related negative consequences at alarming rates. Alcohol use and alcohol-related sex expectancies are predictors of risky sexual behavior among college women; however, African American college women are often underrepresented in empirical studies. The purpose of the present study was to examine the link between alcohol-related sex expectancies (i.e., enhancement, sexual risk taking, and disinhibition expectancies), alcohol use, and risky sexual behavior among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…In the United States, alcohol is the most commonly used substance among adults between the ages of 18 and 24 (Brown et al, 2016). The risk for experiencing negative sex-related consequences such as contracting HIV/AIDS and other STIs, and unplanned pregnancies within this age cohort are heightened (Cottonham et al, 2018;Painter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, alcohol is the most commonly used substance among adults between the ages of 18 and 24 (Brown et al, 2016). The risk for experiencing negative sex-related consequences such as contracting HIV/AIDS and other STIs, and unplanned pregnancies within this age cohort are heightened (Cottonham et al, 2018;Painter et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A woman consuming excessive amount of alcohol may forget to take the pill or use condom at that day. Previous studies in Britain and United States of America [31,42] have demonstrated that women having drinking habit are usually engaged in risky sexual behaviors that expose to unwanted pregnancy and sexually transmitted infection. A systematic review by Terplan et al [43] has also indicated that women with substance use disorders including alcohol used contraception less often than non-substance-users.…”
Section: Discussionmentioning
confidence: 99%
“…The SRS scores for the four subscales in that study demonstrated high internal consistency (α = .78 to .88) and reasonable test–retest reliability ( r = .70 to .90; Turchik & Garske, 2009). SRS scores have demonstrated adequate internal consistency in a sample of Black female college students (α = .74; Cottonham et al, 2018). Cronbach’s alphas for the four subscales in the current study ranged from .75 to .97.…”
Section: Methodsmentioning
confidence: 99%